2004
DOI: 10.1021/jp049865f
|View full text |Cite
|
Sign up to set email alerts
|

Trapping a C2 Radical in Endohedral Metallofullerenes:  Synthesis and Structures of (Y2C2)@C82 (Isomers I, II, and III)

Abstract: Three isomers of yttrium carbide (Y 2 C 2 ) endohedral metallofullerenes, i.e., (Y 2 C 2 )@C 82 (I, II, III), have been synthesized and chromatographically isolated for the first time. The structures of (Y 2 C 2 )@C 82 (I, II, III) metallofullerenes have been characterized by 13 C NMR measurements, whose molecular symmetries have been determined to be C s , C 2V , and C 3V , respectively. In addition, a pure diyttrium metallofullerene, Y 2 @C 82 (III), has also been synthesized and structurally characterized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
163
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(177 citation statements)
references
References 37 publications
14
163
0
Order By: Relevance
“…[97] In a similar way, theoretical calculations as well as 13 C NMR spectroscopy and refined X-ray structural analyses have revealed over the past years other metallic carbide EMFs such as Y 2 C 2 @C 82 (isomers C s , C 2v , and C 3v ), Ti 2 C 2 @C 78 (D 3h ), Sc 2 C 2 @C 68 (C 2v ), Sc 2 C 2 @C 82 (C 3v ), Sc 3 C 2 @C 80 (I h ), and Gd 2 C 2 @C 92 (D 3 ). [36,37,[98][99][100][101][102][103][104][105][106] Interestingly, among all of these EMFs, only Sc 2 C 2 @C 68 (C 2v ) was found to have a non-IPR carbon cage. [104] Crystallographic data together with calculations have strongly suggested that the metallic carbide unit is more stable in the bent geometry.…”
Section: Metallic Carbide Emfsmentioning
confidence: 99%
“…[97] In a similar way, theoretical calculations as well as 13 C NMR spectroscopy and refined X-ray structural analyses have revealed over the past years other metallic carbide EMFs such as Y 2 C 2 @C 82 (isomers C s , C 2v , and C 3v ), Ti 2 C 2 @C 78 (D 3h ), Sc 2 C 2 @C 68 (C 2v ), Sc 2 C 2 @C 82 (C 3v ), Sc 3 C 2 @C 80 (I h ), and Gd 2 C 2 @C 92 (D 3 ). [36,37,[98][99][100][101][102][103][104][105][106] Interestingly, among all of these EMFs, only Sc 2 C 2 @C 68 (C 2v ) was found to have a non-IPR carbon cage. [104] Crystallographic data together with calculations have strongly suggested that the metallic carbide unit is more stable in the bent geometry.…”
Section: Metallic Carbide Emfsmentioning
confidence: 99%
“…This would be consistent with a separate 13 C NMR study that showed that Y 2 C 2 @C 82 and Y 2 @C 82 have the same C 82 [C 3v ] cage. 67 The electronic structure of this compound was established by DFT calculations 64 to be (Sc 2 C 2 ) 4 þ C 82…”
Section: Multimetallofullerenes M 2 @C 2n and Metal Carbide Endohedralmentioning
confidence: 99%
“…[2][3][4] EMFs are stabilized by charge transfer from the internal metal cluster to the carbon cage, which becomes negatively charged. Apart from encapsulating single metal atoms, EMFs are also found with more than one metal atom (M 2 and M 3 ), [5][6][7][8][9][10][11][12][13][14] metal carbides (M 2 C 2 and M 3 C 2 ), [15][16][17][18][19][20][21][22][23] metal nitrides (M 3 N), [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] or even metal oxides (Sc 4 O 2 ), [41] in which M is a Group 3 or lanthanide metal atom. Interestingly, the carbon cages present in EMFs are different from those observed as empty fullerenes and in some cases they do not fulfill the isolated pentagon rule (IPR).…”
Section: Introductionmentioning
confidence: 99%